Determinant and priority factors of innovation for the development of nations - Alcides Barrichello; Emerson Gomes dos Santos; Rogério Scabim Morano (Innovation & Management Review, 2020)
Purpose - This study aims to identify the countries' innovation factors that are determinant for them to achieve higher levels of development. In addition, the research identified which of these factors should be prioritized so the countries can move up in the rank of the most competitive. Design/methodology/approach The study used the indicators of innovation and the stage of development of 137 countries proposed by the Global Competitiveness Report published by the World Economic Forum and techniques of multivariate data analysis. Findings The results indicated that all the factors tested are determinant to lead the countries throughout their stages of development. The research highlights that the factors "Quality of scientific research institutions" and "Patent Cooperation Treaty (PCT) patent applications" should be equally prioritized for the countries' development. Practical implications The results suggested that the factors Capacity for Innovation, Quality of Scientific Research Institutions, Company Spending on Research and Development (R&D), University-Industry Collaboration in R&D, Government Procurement of Advanced Technology Products, Availability of Scientists and Engineers and PCT Patent Applications are decisive for positioning countries in terms of their stage of development and should be part of their public policy and enterprises' strategic planning. Originality/value The findings show that countries should prioritize the factors Quality of Scientific Research Institutions and PCT Patent Applications, as these factors, when acting together, predict the evolution to higher stages of development.
Keywords: 650; Development of nations; Development stages of nations; Innovation and stages of development